Swimming world records - Jokl, E. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
Figure 1 shows the development of the world record in 400 M free style swimming since the beginning of the century, for men and women. Similarly continuous performance improvements have occurred in all sports. During the past hundred years or so, we have been living in an expanding athletic universe. Nevertheless, the performance growth in swimming is characterized by several features : there is the unique closeness of the best performances of women to those of men ; and the conspicuous steep climb of the women's world record curves during the past decade. The best girl swimmers today are as good as were the world record holders in men's events in the 50's. Velocity in swimming races over longer distances do not decline at the same rate as it does in running (Figure 2). Altogether swimming is in an earlier "evolutionary" phase than track and field in which the asymptotic or "flattening-out" portion of world record growth curves are about to be reached --e.g. in the 110 M hurdles, the 5,000 and the 10,000 M, the high jump, the long jump, and the shot put. In fact most performance improvements in track and field events at present are due less to physiological than to technological factors, e.g. the introduction of the tartan track, the fiberglass pole, and foam rubber landing cushions. Comparable innovations are of course in evidence also in swimming, but here they do not play a comparable role. The very fact that the majority of mankind cannot swim, at least not swim for more than a minute or two, speaks for itself. Nevertheless, as recently as in 1960, the Olympic Games· competitions were held in an open air pool. The completion of the magnificent indoor swimming stadium for the 1964 Games in Tokyo represented a milestone in the development of swimming.